1964
DOI: 10.1037/h0042923
|View full text |Cite
|
Sign up to set email alerts
|

Personality variables and counselor-client affect.

Abstract: Measures of client and counselor autonomy, alienation and withdrawal, and guardedness, and the interaction;, of these variables between the client and his counselor were employed as predictor variables in an analysis of regression design where several estimates of counselor-client affect were offered as criterion variables. The counselor and client samples (18 and 121, respectively) were drawn from 8 university counseling centers and the measures were obtained for initial interviews only. The combined levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Recently, however, Williams (1962) demonstrated that significant changes in perceptual congruence among the concepts of Self, Ideal Self and Ordinary Person occurred as a result of brief vocational-educational counseling. It has also been shown that client-counselor similarity in personality has measurable and significant effects in brief counseling with college students (Tuma & Gustad, 1957;Mendelsohn & Gellar, 1963;Canon, 1964).…”
mentioning
confidence: 99%
“…Recently, however, Williams (1962) demonstrated that significant changes in perceptual congruence among the concepts of Self, Ideal Self and Ordinary Person occurred as a result of brief vocational-educational counseling. It has also been shown that client-counselor similarity in personality has measurable and significant effects in brief counseling with college students (Tuma & Gustad, 1957;Mendelsohn & Gellar, 1963;Canon, 1964).…”
mentioning
confidence: 99%
“…Additional References: Canon (1964); Demos (1964); Gonyea (1963); Pool (1965); Richardson (1964 in four individual and four group meetings throughout the school year.…”
Section: Counselor Modelsmentioning
confidence: 99%
“…Apparently, little has been done to follow up this rather imaginative approach, however. Cannon (1964) was one of the few researchers to use those of Snyder's Affect Scales appearing in Snyder'S 1961163 revision. Cannon attempted to determine, as Snyder had, the similarity of personality of counselors and clients expressing positive attitudes toward each other, but the results were somewhat inconclusive.…”
Section: Use Of the Snyder System: A Review Of Some Significant Studiesmentioning
confidence: 99%